2007
DOI: 10.1002/ijc.23168
|View full text |Cite
|
Sign up to set email alerts
|

Nijmegen Breakage Syndrome mutations and risk of breast cancer

Abstract: Mutations in the NBS1 gene have been identified as disease-causing mutations in patients with Nijmegen Breakage Syndrome (NBS), but their clinical impact on breast cancer susceptibility has remained uncertain. We determined the frequency of 2 NBS mutations, 657del5 and R215W, in two large series of breast cancer cases and controls from Northern Germany and from the Republic of Belarus. The 5-bp-deletion 657del5 was identified in 15/1,588 cases (0.9%) from Belarus and in 1/1,076 cases (0.1%) from Germany but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 33 publications
2
99
0
Order By: Relevance
“…Mutant NBS1 carriers have a 3-fold to 9-fold increased risk of breast cancer, although this varies with ethnic background (18,19). Moreover, epidemiologic studies have indicated that a reduced expression of NBS1 is observed in up to 80% of breast cancer cases without any reported mutations (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant NBS1 carriers have a 3-fold to 9-fold increased risk of breast cancer, although this varies with ethnic background (18,19). Moreover, epidemiologic studies have indicated that a reduced expression of NBS1 is observed in up to 80% of breast cancer cases without any reported mutations (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…NBS1 mutant carriers also have a high risk for solid tumors, including breast cancer (18)(19)(20). Cells derived from such patients show defects in cellular responses to the presence of DNA doublestrand breaks (DSB), such as homologous recombination repair (21,22) and an abnormal regulation of checkpoints (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…26 Recently, a 5 bp deletion in NBN (657del5) was shown to be associated with an almost threefold increase in breast cancer risk for heterozygous female carriers in Central and Eastern Europe. 18 Finally, some studies reported an elevated breast cancer risk in hereditary non-polyposis colorectal cancer (HNPCC/ Lynch syndrome, MIM no. 120435) caused by heterozygous mutations in DNA mismatch repair genes, mainly MLH1, MSH2, MSH6 and PMS2, 27,28 whereas other investigations showed no or only a slightly increased breast cancer risk.…”
Section: Breast Cancer-associated Cancer Predisposition Syndromesmentioning
confidence: 99%
“…Breast Cancer Susceptibility Gene List [8,9,11,13,17,19,20], [35][36][37][38][39][40][41][42][43][44][45][46][47] …”
Section: Additional Filementioning
confidence: 99%